Wintering in Europe instead of Africa enhances juvenile survival in a long-distance migrant. (April 2017) - Rotics, Shay; Turjeman, Sondra; Kaatz, Michael; Resheff, Yehezkel S.; Zurell, Damaris; Sapir, Nir; Eggers, Ute; Fiedler, Wolfgang; Flack, Andrea; Jeltsch, Florian; Wikelski, Martin; Nathan, Ran
Abstract : Increased human-induced environmental changes and global warming alter bird migration timing and routes. Recently, many Holarctic species, including white storks, Ciconia ciconia, were reported to overwinter at higher latitudes, closer to breeding grounds. We aimed to understand the causes and implications of this phenomenon by examining bird survival and behaviour during overwintering in Europe versus Africa. We compared GPS and body acceleration data of 54 juvenile (first-year) white storks that originated from the same European natal population and overwintered in Europe or Africa. All six juveniles that overwintered in Europe survived through their first year, which was significantly higher than only 38% of the 48 overwintering in the species' traditional grounds in Africa. During overwintering, storks in Europe differed from those in Africa by (1) reducing movement and foraging range, (2) spending less time flying and more time resting, thus using less energy (estimated from overall dynamic body acceleration) and (3) reducing foraging effort, while relying more on anthropogenic resources (landfills and agricultural areas). Timing affected overwintering site as juveniles that overwintered in Europe hatched and started migrating later. We emphasize, however, that late hatching by itself did not yield a survival benefit as not all late juveniles curtailed their migration. We suggest that wintering in Europe was less demanding compared to Africa which may explain the increased survival of juveniles that wintered in Europe. Our findings correspond to the general increase in the European wintering population of white storks, and shed light on the contemporary trend of shortened bird migration; a phenomenon with potentially broad ecological implications. Highlights: Of the studied juvenile storks 5% wintered in Europe instead of migrating to Africa. Birds wintering in Europe had higher survival than conspecifics in Africa. In Europe, birds moved less and expended less energy than in Africa. Juveniles in Europe relied more on anthropogenic resources. These behavioural and habitat differences may underlie wintering survival disparity.